COVID-19 Impact Monitoring : Malawi, Round 7 - World Bank (World Bank, Washington, DC, 2021)
In May 2020, the National Statistical Office (NSO), with support from the World Bank, launched the High-Frequency Phone Survey on COVID-19, which tracks the socio-economic impacts of the pandemic on a monthly basis for a period of 12 months. The survey aimed to recontact the entire sample of households that had been interviewed during the Integrated Household Panel Survey (IHPS) 2019 round and that had a phone number for at least one household member or a reference individual. This report presents the findings from the seventh round of the survey that was conducted during the period of January 20 - February 6, 2021.